2013
DOI: 10.1038/ncomms3435
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes on a spider silk scaffold

Abstract: Understanding the compatibility between spider silk and conducting materials is essential to advance the use of spider silk in electronic applications. Spider silk is tough, but becomes soft when exposed to water. Here we report a strong affinity of amine-functionalised multi-walled carbon nanotubes for spider silk, with coating assisted by a water and mechanical shear method. The nanotubes adhere uniformly and bond to the silk fibre surface to produce tough, custom-shaped, flexible and electrically conducting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
117
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 35 publications
3
117
0
1
Order By: Relevance
“…Spider silks can be stronger than steel and tougher than Kevlar, yet are much lighter weight than these manmade materials 4 . Silks vary in extensibility 5 , are temperature resilient 6 , can enable electrical conduction 7 , and can inhibit bacterial growth while being nearly invisible to the human immune system 8 . Thus, novel materials derived from spider silks offer tremendous potential for medical and industrial innovation.…”
mentioning
confidence: 99%
“…Spider silks can be stronger than steel and tougher than Kevlar, yet are much lighter weight than these manmade materials 4 . Silks vary in extensibility 5 , are temperature resilient 6 , can enable electrical conduction 7 , and can inhibit bacterial growth while being nearly invisible to the human immune system 8 . Thus, novel materials derived from spider silks offer tremendous potential for medical and industrial innovation.…”
mentioning
confidence: 99%
“…
wileyonlinelibrary.com

such as transistor, [ 5 ] triboelectric, [ 6 ] capacitive, [ 7,8 ] piezoelectric, [9][10][11] and piezoresistive properties.

Piezoresistive pressure sensors, which transform an input force into an electrical signal caused by the change in the resistance, have attracted considerable attentions by virtue of its simplicity and low cost in design and implementation. Most fl exible piezoresistive sensors are prepared by loading conductive nanomaterials (e.g., carbon nanotubes (CNTs), [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] graphene, [29][30][31][32] nanowires, [33][34][35] nanoparticles) onto fl exible substrates (e.g., fi bers, [ 12,13 ] fi lms, [14][15][16][17] opencell foams [ 29 ] ) via a number of processing methods, such as blending, [ 19,20 ] coating, [ 21,29 ] and printing. [ 17 ] Among the different conductive nanomaterials, carbon nanotubes have attracted a considerable amount of att...

…”
mentioning
confidence: 99%
“…The effective properties of the ultralight cellular materials are defined both by their cell geometry (that is, the spatial configuration of voids and the solid) and the properties of the solid constituents (for example, strength, continuity and so on) [9][10][11] . In natural structures, it has been demonstrated that introducing a continuous fibrous structure can substantially improve material utilization and the resultant properties [12][13][14] . For instance, spider webs possess a relative density similar to that of ultralight aerogels but are clearly structurally robust 15 .…”
mentioning
confidence: 99%